Utilization of Ca/Si/Fe3O4 Magnetic Composite as a Solid Catalyst in Transesterification of Waste Cooking Oil - Rehan, Zainol Abidin (2015)

(untitled)
In this research, transesterification of waste cooking oil to methyl ester is being studied with the aid of Ca/Si/Fe3O4 as a solid magnetic composite catalyst. This catalyst was produced by using waste source to reduce the cost. By using heterogeneous catalyst, some environmental problem can be avoided since the catalyst can be reuse and the final product is easy to separate. As we may know, biodiesel is non-toxic, environmental friendly, high lubricity, biodegrable and renewable. In this study, waste cooking oil is used as a feedstock in producing the promising fuel, which is biodiesel. It thus could encounter many environmental issues since waste feedstock is being used. Preparation of methyl ester using waste feedstock and with the aid of Ca/Si/Fe3O4 should be properly studied since it is worth to be investigated.